The Role of Thyroid Hormones on Skeletal Muscle Thermogenesis - Nadia Sawicka-Gutaj (Metabolites, 2022)
Nowadays obesity becomes a significant global problem. Hence, recently more and more attention has been paid to substances present in the body that have a significant impact on metabolic processes and thermogenesis, in the context of their potential use in the prevention and treatment of obesity. It is well known that the relationship between thyroid hormones and obesity is multilayered, however recently, more and more information about the possible relation between thyroid hormones and muscle metabolism has been published. The aim of this review is to present the most updated information on the physiological impact of thyroid hormones on muscle tissue, as well as pathological changes related to the occurrence of various types of thyroid disorders, including hypothyroidism, hyperthyroidism and sick euthyroid syndrome. However, the data in humans still remains insufficient, and further studies are needed to fully explore the thyroid-muscle cross-talk.